2002
DOI: 10.1172/jci0214151
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand-1–deficient mice have impaired leukocyte tethering to E-selectin under flow

Abstract: Introduction Leukocyte recruitment during inflammation is a multistep process involving tethering and rolling of leukocytes on vascular surfaces, followed by firm adhesion and transmigration into the affected tissues (1). Interactions of selectins with glycoconjugate ligands primarily mediate the initial tethering and rolling adhesion of leukocytes (2, 3). L-selectin, expressed on leukocytes, binds to ligands on other leukocytes and on activated endothelial cells. P-selectin, expressed on activated platelets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 61 publications
11
168
1
Order By: Relevance
“…If it is found that P-selectin and E-selectin can utilize endoglycan as a ligand, as is strongly suspected from its parallels to PSGL-1, the range of potential in vivo functions for this molecule would be further broadened since these selectins are found on platelets and/or activated vascular endothelium. Gene targeting approaches (52,53) and antibody blockade studies (49) have been essential in establishing the importance of PSGL-1 as a selectin ligand. Similar approaches will be necessary to gain a further understanding of endoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…If it is found that P-selectin and E-selectin can utilize endoglycan as a ligand, as is strongly suspected from its parallels to PSGL-1, the range of potential in vivo functions for this molecule would be further broadened since these selectins are found on platelets and/or activated vascular endothelium. Gene targeting approaches (52,53) and antibody blockade studies (49) have been essential in establishing the importance of PSGL-1 as a selectin ligand. Similar approaches will be necessary to gain a further understanding of endoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…10 Antibody blockade of the N-terminal region of PSGL-1 inhibits rolling of leukocytes on P-selectin and L-selectin in vivo. 12,13 Elimination of PSGL-1 by gene targeting and homologous recombination reduces the number of neutrophils interacting with the endothelium, 14,15 alters the rolling velocity on P-selectin and on E-selectin, 14,16 and diminishes neutrophil recruitment into inflamed tissue. 15 In addition to its adhesive function, PSGL-1 is also known to initiate intracellular signaling events upon ligand engagement.…”
Section: Psgl-1mentioning
confidence: 99%
“…The leukocyte mucin P-selectin glycoprotein ligand-1 (PSGL-1) is the dominant ligand for P-and L-selectin and an important ligand for E-selectin. 3,4 The manner in which selectins or their ligands distribute on cell surfaces has major influence on rolling behavior. 5 For example, L-selectin and PSGL-1 are located on tips of microvilli, 6,7 which enhances the initial tethering of leukocytes.…”
Section: Introductionmentioning
confidence: 99%